Free Time For Wellness: a co-designed intervention utilizing social networks to encourage physical activity for cancer prevention among low resourced mothers - Lauren C. Houghton; Marley P. Gibbons; Jeanette Shekelle; Ingrid Oakley-Girvan; Jessica L. Watterson; Kate Magsamen-Conrad; Cheryl Jones; Kajal Gokal (BMC, 2021)
Abstract Background Physical activity is central to chronic disease prevention. Low resource mothers face structural barriers preventing them from increasing their physical activity to reduce their chronic disease risk. We co-designed an intervention, with the ultimate goal of building social cohesion through social media to increase physical activity for low resourced mothers in urban settings. Methods In 2019, we interviewed 10 mothers of children (< 12 years) living in Washington Heights, Manhattan. The interviews were transcribed and coded for themes that guided the creation of a co-design workshop. Washington Heights-based mothers (n = 16) attended a co-design workshop to generate the blueprint for the Free Time for Wellness intervention. Results Mothers in our sample had limited time, external support and resources, which hindered them from increasing their physical activity; we learned that in addition to physical health, mental health was a concern for participants. Participants had varying degrees of self-efficacy and trust in social media. Bringing mothers and researchers together in a co-design workshop, we identified types of physical activities they would enjoy participating in, the ideal time to do so, the kind of childcare they needed, and their preferences for communication with the community champion. The interviews and workshop highlighted the need for a community space that mothers and children could co-occupy. The intervention was designed to be 3 months' worth of sample programming with one activity per week, rotating between dance, yoga, food pantry visits and group playdates. Participants were invited to bring their children to a space with one room for the 'participants only' activity and a second room in which professional childcare providers supervised the children. Conclusions Through this two-phased co-design process, we created an intervention with mothers in an urban community with the goal of using social media to bring them together for wellness, primarily through increased physical activity. Despite the co-design of this intervention with a specific community, there are some universal applications of our findings, and of the use of co-design workshops, to other settings.